Knowledge Integration Within Japanese Firms: The Fujitsu Way - Mohannak, Kavoos (Journal of Knowledge Management Practice, 2011)
The paper analyses knowledge integration processes at Fujitsu from a multi-level and systemic perspective. The focus is on team-building capability, capturing and utilising individual tacit knowledge, and communication networks for integrating dispersed specialist knowledge required in the development of new products and services. The analysis shows how knowledge integration is performed by Fujitsu at different layers of the company.